PENGARUH PERBANDINGAN KENTANG KUKUS DENGAN TERIGU TERHADAP KARAKTERISTIK FLAKES - Rahmadani, Kadek Ari; Wisaniyasa, Ni Wayan; Widpradnyadewi, Putu Ari Sandhi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 1 (2016): Jurnal ITEPA, 2016)
The aims of this research was to determine the effect comparison steamed potatoes and wheat on characteristics flakes, and to know the exact comparison between steamed potatoes and wheat which is able to produce flakes with the best characteristics. This research used a completely randomized design with treatments such as comparison between steamed potatoes and wheat are 30% steamed potatoes : 70% wheat, 40% steamed potatoes : 60% wheat, 50% steamed potatoes : 50% wheat, 60% steamed potatoes : 40% wheat, and 70% steamed potatoes : 30% wheat. Each treatment was repeated three times to obtain 15 units of experiments. Data were analyzed by analysis of variance and if the treatment effect on the observed variable then followed by Duncan test. The results showed comparison of steamed potatoes with wheat highly significant effect on water content (1.87% - 2.84%), ash content (2.24% - 2.74%), fat content (7.25% - 8.11%), protein content (7.46% - 8.47%) and color (5.33 - 6.33), has significantly effect on the taste (5.86 - 6.33) and overall acceptance (5.86 - 6.40), while no significant effect on carbohydrate content, texture, and aroma. Comparison of 70% steamed potatoes with 30% wheat produce flakes with the best characteristics, water content 2.84%, ash content 2.74%, protein content 7.46%, fat content 7.25%, carbohydrate content 79.69%, color 6.13 (like), texture 5.53 (like), aroma 5.66 (like), taste 6.26 (like), and overall acceptance 6.33 (like).
Keywords: potato, wheat, characterics, flakes